Investigation on the Strength Activity of Grinding Sand and Its Effects on the Physical Properties of FiCO OPC-Grinding Sand Mortar - Vu, Hoang Tung; Ho, Thanh Su (Old Journal, 2019)
Sand is an important constituent of a large proportion of mortar and concrete, but it is mainly used in the form of natural, used in the form of a fine grinding not well researched. In addition, the fine-grained sand and aggregate are highly activeness, so this can be used to produce a mixture of Portland cement, mortar or concrete with higher efficiency. This study investigated the fine-grained sand activity in grain strips